Virgin Coconut Oil Accelerates Wound Healing: A Systematic Review - Eliza Arman; Almahdy Almahdy; Putri Dafriani; Dedy Almasdy (GLOBAL HEALTH SCIENCE GROUP, 2025)
Virgin Coconut Oil (VCO) has been shown to have significant therapeutic benefits for skin wound healing, primarily due to its anti-inflammatory effects, ability to stimulate tissue regeneration, and potent antioxidant properties. This review analyzes the available research exploring the relationship between VCO and its impact on wound healing. A comprehensive search was conducted using the Medline database via PubMed and Scopus to identify relevant studies published between 1970 and March 2023. The main inclusion criteria were original articles written in English that evaluated wound healing in in vivo skin models using topically applied VCO. The search initially yielded 689 articles, but only 4 articles met these criteria. These studies addressed various types of wounds, including excisional, burn, and diabetic wounds. All four studies demonstrated positive outcomes, showing that VCO promotes skin wound healing. The oil’s anti-inflammatory, antioxidant, and antibacterial properties were identified as key contributors to its role in enhancing the wound healing process.